Studi Kasus Perilaku Membolos Dua Siswa SMK - Cahya Adi Nugraha; Rian Rokhmad Hidayat; Agus Tri Susilo (Jurnal Psikoedukasi dan Konseling)
Abstract: The purpose of this study was to determine the concrete form of truancy behavior, the causal factors behind truancy students, and the impact on personal, social, and learning aspects arising from truancy behavior. This research is qualitative research with a case study method. Researchers collected data through interviews and document observations related to truancy behavior. The study results show that the form of truancy behavior carried out is not attending school without permission and leaving school when learning hours are still in progress. The causative factors behind this behavior come from family, environment, peers, and self factors. The peer factor is the most influential. The impact on the personal aspect is making students lazy and not enthusiastic about participating in learning activities. The impact on the social aspect is that students fall into a hostile social environment. Meanwhile, the impact of learning is a low achievement and a lack of understanding of the subject matter.